Akurasi Sistem Penjadwalan Sholat Digital Menggunakan Arduino Sebagai Pengendali - Emil Naf’an (Rektorat Universitas Putra Indonesia YPTK Padang, 2019)
This study aims to test the accuracy of the Digital Prayer scheduling system using the Arduino as a controller. The place of research is the scheduling of Digital Prayers at the Putra Putra University Mosque (UPI) of the Padang College of Computer Foundation (YPTK). Prayer schedule data is taken from the website of the Indonesian Ministry of Religion and scheduling routine lecturer activities every morning. Data is stored on a MicroSD card with a different data file name. Data is processed using the Arduino module. The data tested is the display of prayer schedules on Seven Segments and lecturer activity schedule displays on Running Text. The prayer times automatically work with the date and time display (hours, minutes, seconds) starting from the Fajr prayer to the Isha prayer at Seven Segments. Display the activity of lecturer routines automatically by displaying the names of lecturers with the specifications of their assignments, such as reading the Qur'an, reciting Asmaul Husna and praying. Testing is done by activating the equipment for a week (7 days) non stops. The system is tested in terms of the durability of components in operation, the timeliness in activating Buzzer when prayer time has entered and scheduling lecturer activities very well, precisely and accurate. Thus the system can be used and produced on a larger scale.